Oline Learning Model to Improve Student's Practical Skills in Batik Course - Asih, Dwi Putri; Syamwil, Rodia; Qudus, Nur (Universitas Negeri Semarang, 2021)
Batik course is practical learning which effectively applies by face-to-face learning method. However, batik learning activities cannot run effectively during the disaster (covid-19) period. This study aims to determine the improvement of students' batik skills with an online learning model in batik courses at the Faculty of Engineering, State University of Semarang. This research is a type of research and development. The development procedure in this study adapted from the ADDIE model, which includes the analysis phase of preliminary studies and literacy, drafting of learning models, development of learning models, application of learning models to research subjects, and product revision. The data analysis technique used in this research is descriptive statistics. The research subjects consisted of an experiment group of 10 students and a control group of 10 students. Based on the results of the expert validation of the learning model, all indicators approve with some improvements. Analyzed the effectiveness based on trials was through the impact of student learning outcomes in batik subjects. The average learning outcomes of the experiment group had a relatively higher score of 85.3, and the control group was 80.1. In comparison, the N-Gain value is 64%, which means that the online learning model of batik learning is quite effective in improving learning outcomes and solutions for implementing practical knowledge during disaster periods.